Conceptual Issues in Second Language Research in Africa - Are, Olushola Bamidele (Linguistik Online, 2013)
This paper is an overview of some of the complications associated with conceptualizing second language in African societies, particularly with reference to European languages. Most popular opinions and many scholarly insights appear to define second language mainly in terms of sequence of acquisition. From this perspective, the term second language refers to a language learnt in addition to a previously acquired one. While this view of second language actually applies to many African situations, there are complex bilingual and multilingual situations in Africa that pose serious conceptual problems when viewed from the standpoint of this dominant view. This paper raises the need for scholars to be conscious of these situations, and the variations in the conception of second language that consequently exist, so that divergent perspectives of second language can be better accommodated in the emerging global academic community.